Evaluation of Pollution Indices of Heavy Metals in Ceiling Fan Dust in Lecture Halls of a Tertiary Institution, Calabar, Nigeria - C. A. Ushie; A. A. Abong; E. O. Obi (Journal of Applied Sciences and Environmental Management, 2023)
This study evaluated heavy metals in ceiling fan dust in five (5) lecture halls of a tertiary institution in Cross Rivers State, Calabar, Nigeria using appropriate standard techniques. Data obtained reveal that contamination factor for Zn, Cu, Fe, Mn, Cr, Ni and Pb were all < 0.10 indicating very slight contamination, while the geoaccumulation index for Zn, Cu. Fe, Mn, Cr, Ni and Pb were ≤ 0 indicating non – contamination. Nemerow integrated pollution index (NIPI) for Zn, Cu, Fe, Mn, Cr, Ni and Pb were all ≤ 0.7 which indicates non – pollution, while Cd showed high level of pollution with values NIPI > 3 in all sampled sites. Enrichment factor for Zn, Cu, Mn, Cr, Cd, Ni and Pb in all the sites were >1000 which indicates that all the heavy metals were from artificial source. Generally, the findings of the study revealed that the lecture halls are polluted with cadmium (Cd) mainly from artificial source while other heavy metals such as Zn, Cu, Fe, Mn, Cr, Ni and Pb were within the permissible limits of the indices. It was recommended that ceiling fans should be regularly and thoroughly cleaned to prevent pollution by heavy metals. Also, there should be awareness campaign for users of lecture halls on the health risk associated with ceiling fan dust.